Roadmap for Creating Effective Communication Tools to Improve Health Equity for Persons With Intellectual and Developmental Disabilities - Dharampuriya, Priyanka R.; Abend, Susan L. (Frontiers in Health Services, 2022)
Persons with intellectual and developmental disabilities (IDD) live 20 fewer years than the average person and almost 40% of their deaths are from preventable causes. They suffer from well-documented disparities in health and healthcare, and much of this inequity is rooted in information transfer failures between patients, their caregivers, and their healthcare providers. Tools to improve communication between these stakeholders, such as health checks and hand-held health records, or health passports, have been implemented in Europe, Australia and Canada with mixed results, and there are no standard information tools currently in widespread use in the U.S. We review the evidence of the effectiveness of these tools, as well as their barriers to adoption, to inform proposed development of next-generation information transfer tools most useful to patients with IDD and their healthcare providers. The repair of health information transfer failures will be a major step toward achieving health equity for this population.